2020
DOI: 10.1097/nnr.0000000000000417
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Continuity at Discharge and Return to Hospital

Abstract: Background Promoting continuity of nurse assignment during discharge care has the potential to increase patient readiness for discharge—which has been associated with fewer readmissions and emergency department visits. The few studies that examined nurse continuity during acute care hospitalizations did not focus on discharge or postdischarge outcomes. Objectives The aim of this research was to examine the association of continuity in nurse assignment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Future studies will need to assess the relative value of the discharging nurse conducting the assessment or another member of the discharge team such as the discharge coordinator or case manager. Of note, we found in another of our studies that patients who had continuity of care from their discharging nurse (when the patient received care from the same nurse on the day of and day before discharge) had lower readmission rates than those without this continuity (Bahr et al., 2020).…”
Section: Discussionmentioning
confidence: 67%
“…Future studies will need to assess the relative value of the discharging nurse conducting the assessment or another member of the discharge team such as the discharge coordinator or case manager. Of note, we found in another of our studies that patients who had continuity of care from their discharging nurse (when the patient received care from the same nurse on the day of and day before discharge) had lower readmission rates than those without this continuity (Bahr et al., 2020).…”
Section: Discussionmentioning
confidence: 67%
“…In relation to our study, we found an additional characteristic that influenced patient expectations as a component of hospital discharge readiness: it was mostly male patients who had a higher need for more information about their disease and its treatment.The education of patients, carried out duringhospitalization after myocardial infarction, should be planned, monitored and conducted by all members of the therapeutic team in accordance with their competences [ 20 ]. Some studies have indicated that the continuity of nurse assignment during discharge care has the potential to increase patient readiness for discharge, which has been associated with fewer readmissions and emergency department visits [ 21 ]. Other research suggests the need for a structured process for discharging a patient from hospital, with tools to help healthcare organizations improve their discharge process and decrease readmission rates [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the nurses' experiences were calculated based on the time when the nurse was appointed as a full-time nurse as recorded in the hospital database, which could differ from the actual length of their careers. Finally, there may be other nursing factors that affect patient outcomes, such as education or burnout (Bahr et al, 2020;Jun et al, 2021;Stifter, Yao, Lodhi, et al, 2015), which could not be analysed in the current study. Therefore, in the future, outcome research on nurse continuity should be studied to help address some of these limitations.…”
Section: Limitationsmentioning
confidence: 99%
“…However, low nurse continuity was directly related to a decrease in the clinical status of adult patients admitted to medical‐surgical units, as measured by the Rothman Index (Yakusheva et al, 2017). Furthermore, it has been found that high nurse continuity significantly reduced 30‐day readmission rates (Bahr et al, 2020) and it was a predictor of high levels of patient or caregiver satisfaction (Miedaner et al, 2016; Tonkikh et al, 2020). While studies on nurse continuity have begun to reveal its positive impact on patient outcomes, there is limited research on the application of continuity of care for surgical patients.…”
Section: Introductionmentioning
confidence: 99%